Determination of change of direction deficit thresholds across a spectrum of angles in basketball players - Barrera-Domínguez, F. J.; Jones, P. A.; Almagro, B. J.; Molina-López, J. (Journal of Sports Sciences, 2024)
Change of direction deficit (CODD) offers valuable insights into a player`s balance between linear and multidirectional speed. However, there are still no established reference values for CODD. The objectives of this study were to determine CODD thresholds for various change of direction angles in basketball players according to gender and analyse the relationships between CODD and execution time in speed tests. One hundred and thirty basketball players (46% female; age: 23.7 ± 5.29 years; height: 189.1 ± 11.1 cm; body mass: 84.3 ± 15.7 kg) undertook 10-m linear and change of direction speed test at 45º, 90º and 180º. A k-means cluster analysis was conducted to standardise CODD thresholds and a one-way analysis of variance to identify the differences between clusters. The results revealed angulation-specific CODD thresholds, ranging from 3% to 8%, 17% to 25% and 43% to 51% for 45º, 90º and 180º cutting angles, respectively for the pooled sample. Furthermore, differences inter-clusters (p < 0.05) were observed for execution time at all cutting angles for both genders. Therefore, strength and conditioning coaches are encouraged to assess CODD as a highly valid variable for evaluating change of direction performance and to use current CODD thresholds to tailor training programmes according to each athlete`s needs.